University hygiene in the context of the implementation of “the law on higher education”: physiological and hygienic bases and ways of development - Serheta, I.V.; Panchuk, O.Ye.; Stoian, N.V.; Drezhenkova, I.L.; Makarov, S.Yu. (Environment & Health, 2016)
Objective: We analyzed the most actual problems of the university hygiene, determined the physiological and hygienic foundations of their adequate solution, substantiated the scientific principles of the implementation of health protection technologies, hygienic standards of motor activity and profession-graphic assessment of the features of the girls’ and boys’ professional activities, mastering the basic medical and stomatological specialities. Materials and methods: We performed our research with the help of modern hygienic, medical and sociological, psychophysiological, psychodiagnostic, epidemiological, psychological and pedagogical methods and methods of expert assessments and statistical analysis on the basis of Vinnytsia National M.I. Pyrohov Medical University. Results: Analysis of the most actual problems of the university hygiene as an important direction in the hygienic science was carried out, physiological and hygienic bases for their adequate solution were defined. Hygienic standards of the students’ motor activity in the higher educational institutions were developed, taking into account the peculiarities of social formation and professional development of the future specialists and providing a positive effect on the processes of the formation of the health state and functional possibilities of their organism: values of diurnal energy – 11500-13500 kJ in boys and 9000-11000 kJ in girls; amount of locomotions in the daily cycle –15000-19000 steps in boys and 14000-18000 steps in girls; length of the dynamic component in the daily time budget – 140-190 minutes in boys and 130-180 minutes in girls. The structural components of psychophysiograms and psychograms of the leading stomatologic specialities, causing a high level of the professional suitability of the students, were determined and informative physiological criteria for the assessment of the efficiency of mental activity and adaptation possibilities of the students were established. Psychohygienic bases of the health protection technologies in the higher educational institutions with the following conceptual principles as: regime-adaptation, psychophysiological, personal and integrative-functional principles with a relevant content, positively affecting the processes of health formation and providing a high level of the training readiness of modern students, were scientifically substantiated.